2010
DOI: 10.4081/ejh.2010.e2
|View full text |Cite
|
Sign up to set email alerts
|

Shared Y chromosome repetitive DNA sequences in stallion and donkey as visualized using whole-genomic comparative hybridization

Abstract: The genome of stallion (Spanish breed) and donkey (Spanish endemic Zamorano-Leonés) were compared using whole comparative genomic in situ hybridization (W-CGH) technique, with special reference to the variability observed in the Y chromosome. Results show that these diverging genomes still share some highly repetitive DNA families localized in pericentromeric regions and, in the particular case of the Y chromosome, a sub-family of highly repeated DNA sequences, greatly expanded in the donkey genome, accounts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…This technique has provided evidence for the presence of polymorphisms in insects where knowledge about the presence of these polymorphisms was low and mainly constrained to variations in C-banded regions. 13 In mammalian species, unexplored polymorphisms were identified in swine, sheep, stallion, and donkey, 14 16 and the technique also provided evidence for the presence of highly conserved repetitive DNA sequences on chromosome 9 when human and gorilla chromosomes were compared. 17 Accordingly, W-CGH is a reliable tool for the comparison of the levels of polymorphism of repetitive DNA sequences in the human genome, giving a one-shot experimental hybridization for comparing two different genomes.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has provided evidence for the presence of polymorphisms in insects where knowledge about the presence of these polymorphisms was low and mainly constrained to variations in C-banded regions. 13 In mammalian species, unexplored polymorphisms were identified in swine, sheep, stallion, and donkey, 14 16 and the technique also provided evidence for the presence of highly conserved repetitive DNA sequences on chromosome 9 when human and gorilla chromosomes were compared. 17 Accordingly, W-CGH is a reliable tool for the comparison of the levels of polymorphism of repetitive DNA sequences in the human genome, giving a one-shot experimental hybridization for comparing two different genomes.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 5 This fraction of the genome seems to escape the selective pressure actings on the non-repetitive segments, representing good evolutionary marker in studies of species evolution, chromosome structure and function, and in the detection of chromosomal rearrangements, supernumerary and sex chromosomes. 6 8 The molecular organization and chromosome location of repetitive DNAs have been analyzed in a large number of fish species. 9 13 These studies have demonstrated the enormous potential that the investigation of repetitive DNAs offers in extending our knowledge of karyotype differentiation in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms due to the accretion of duplicated genomic segments are common in mammalian genomes, in particular at centromeric and telomeric regions where they are usually silenced and show no effect on the phenotype [12][13][14][15]. In mammalian species, unexplored polymorphisms were identified in swine, sheep, stallions, and donkeys [16][17][18], and the technique also provided evidence for the presence of highly conserved repetitive DNA.…”
Section: Discussionmentioning
confidence: 99%